Peaking for maximal strength: Muscular adaptations and performance outcomes - Spencer K. T. (East Tennessee State University, 2021)
The purposes of this dissertation were to 1) determine what tapering and peaking practices appear to be most effective via systematic review, 2) to identify the tapering and peaking practices used by North American powerlifters, 3) to experimentally compare muscular adaptations and performance changes following two different training cessation periods, and 4) to experimentally compare the two most common taper models following a training program aimed at peaking maximal strength. Based on the scientific literature, a step and exponential taper appeared to be the most effective tapering models used when volume-load is reduced by half over 2±1 week. Interestingly, North American powerlifters reported that the step taper was most often used while reducing volume-load by 41-50% over 7-10 days. Furthermore experimentally, there were no changes in lower body maximal strength following 3 or 5 days of training cessation. However, upper body maximal strength decreased following 5 days of training cessation. Thus, at the end of a taper, a training cessation period of 3 days appears to be effective for maintaining upper and lower body maximal strength. Furthermore, a work-matched step taper and exponential taper produced similar outcomes for 1RM back squat, bench press, and deadlift, powerlifting total and Wilks Score in strength athletes, yet deadlift 1RM changes favored the exponential taper. However, there were clear physiological differences observed at the whole muscle and muscle fiber levels that appeared to contribute to performance outcomes. This was one of the first investigations demonstrating whole muscle and muscle fiber hypertrophy following a peaking program in strength athletes. Immunohistochemical and immunoblotting analyses demonstrated an increase in myosin-heavy chain IIA content with concomitant decreases in myosin-heavy chain I and IIX content, particularly following the step-taper. These myosin isoform shifts towards a faster, higher quality phenotype were related to changes in underlying myocellular signaling (i.e. Sox6 upregulation, micro RNA-499a downregulation) responsible for fiber-type transitions. These findings indicate a shorter taper may produce favorable muscular adaptations followed by a period of short-term training cessation to prevent the loss of taper-induced performance adaptations. Overall, the findings from these investigations support the use of tapering to enhance maximal strength.